HUKUM ADAT DI NUSANTARA INDONESIA - Ahmad Tahali (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The law that developed in the midst of the community that today we know as customary law is values that have long been recognized as the norm. These values or norms have long grown in the midst of the Indonesian people, a nation whose people have a diversity of tribes, races, religions and customs that spread throughout the archipelago. The spread of diversity grows values or norms that are recognized in each region that has customary law. Admittedly the customary law has become an automatic way of dealing with it customarily. Customary law is a cultural aspect of society that has values, social norms. Among the benefits of studying customary law is to understand Indonesian legal culture, with this we will know which customary law is no longer in accordance with the times and which customary law can approach uniformity that applies as national law.